Reparative phase events on periodontal disease progression: interpretation and considerations - Suzuki, Thaís Yumi Umeda [UNESP]; Kina, Juliana [UNESP]; Kina, Mônica [UNESP]; Kina, Eunice Fumico Umeda; Kina, José Ricardo (Bioinfo Publications, 2013)
Periodontal disease progress by destructive acute phases intercalated by reparative chronic phases. The aim of this study was to investigate the clinical and histological evidence of the periodontal disease reparative phase by analyzing bone wall conditions inside periodontal pockets and histologic images of periodontal pockets, identified in relevant publications. 81 patients with periodontitis, were randomly assigned into this study. Clinical and radiographic parameters were established to diagnose periodontal disease providing a sample of 133 diseased areas, which were treated by modified Widman flap. Documentation by digital photography were recorded in the surgery. Relevant publications showing histological images of periodontal pockets, were identified in Medline, PubMed and Google data base, were scanned and digitalized. All images obtained were evaluated and the presences of the reparative evidence in the zone around the underlying destroyed alveolar bone were critically analyzed. All periodontal bone defects, showed cortical bone reparations at different levels inside periodontal bone defects. All histologic images of periodontal pockets identified in relevant publications showed repaired gingival-attached connective tissue localized above underlying destroyed alveolar bone. All the evidences analyzed in this study suggested that periodontal disease is predominantly chronic, quiescent, showing reparative phases in different levels.
Keywords: Diagnosis; Evidence-based dentistry; Pathogenesis of periodontal disease; Periodontal surgery; Periodontal regeneration